Spin Qubits in Double and Triple Quantum Dots - Medford, James Redding (Harvard University, 2013)
This thesis presents research on the initialization, control, and readout of electron spin states in gate defined GaAs quantum dots. The first three experiments were performed with Singlet-Triplet spin qubits in double quantum dots, while the remaining two experiments were performed with an Exchange-Only spin qubit in a triple quantum dot. === Physics